2019
DOI: 10.1097/wad.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Complicated Relationship Between Depressive Symptoms and Cognitive Impairment in Preclinical Alzheimer Disease

Abstract: Introduction: The relationships between Alzheimer’s disease (AD), cognitive performance, and depression are poorly understood. It is unclear whether depressive features are a prodrome of AD. Additionally, some studies of aging exclude depressed individuals, which may inappropriately limit generalizability. The aim of the present study was to determine whether depressive symptoms affect cognitive function in the context of preclinical AD. Methods: Cross-sectional multivariate analysis of participants in a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
2
6
0
2
Order By: Relevance
“…Our findings are in line with other studies (Garay, 2007;Plati et al , 2006). Recent studies have shown that over time depression predicts cognitive impairment (Chan et al, 2019;Dean, Oulhaj, Zamboni, Dejager, & Wilcock, 2014) and Alzheimer's disease (Javaherian et al, 2019;Ruthirakuhan et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with other studies (Garay, 2007;Plati et al , 2006). Recent studies have shown that over time depression predicts cognitive impairment (Chan et al, 2019;Dean, Oulhaj, Zamboni, Dejager, & Wilcock, 2014) and Alzheimer's disease (Javaherian et al, 2019;Ruthirakuhan et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…This view is also supported by a review by Mcintyre et al ( 58 ), that posits that a subgroup of individuals with MDD show progressive decline in memory. A study on late-life depression suggested that depressive symptoms were a prodrome for Alzheimer ( 59 ), that could suggest a dementia state effect on reduced memory in late life MDD (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, moderately significant cognitive impairments in executive functions and attention tasks, and minor nonsignificant impairments in memory, were found to persist in patients whose depressive symptoms had remitted, indicating that cognitive impairment occurs separately from episodic depression to major depressive disorder. Some recent studies showed that depression predicts conversion to cognitive impairment over time [117, 118] or the development of AD [119, 120].…”
Section: Discussionmentioning
confidence: 99%